Design, construction and commissioning of an organic Rankine cycle waste heat recovery system with a Tesla-hybrid turbine expander - Cirincione, Nicholas, author; Olsen, Daniel, advisor; Zimmerle, Daniel, committee member; Dandy, David, committee member (Colorado State University. Libraries, 2011)
Issues surrounding energy are some of the most compelling subjects in the world today. With human's ever increasing need for energy, production must increase or consumption must be reduced to avoid an unsustainable long-term energy balance. One part of the energy solution is low-temperature Organic Rankine Cycles (ORCs). ORCs can be utilized to produce power in mass quantity from a dedicated heat source such as a geothermal well. ORCs may also be utilized as a waste heat recovery system to generate power from a heat stream that is typically rejected to the environment. Low-temperature waste heat streams are ubiquitous as every internal combustion engine generates 55-75% of its total fuel energy as waste heat. Efficiency of a waste heat recovery ORC system is strongly dependent on condensing temperature and expander efficiency. Condensing temperatures are typically kept low with an evaporative condensing unit. However, water consumption to increase energy production is becoming less tolerated. To provide a means to conduct research around these issues, a waste heat recovery ORC test bed was designed and constructed. This thesis contains information on construction and operation of the test bed with these features: R245fa working fluid, direct dry cooled condensing and a Tesla-hybrid turbine expander.
Keywords: ORC; waste heat recovery; Tesla; organic Rankine cycle